Petroleum and Gas - Review of Production of Petroleum in the United States in 1926 - James H. Gardner (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1927)
It is a striking fact in the domestic oil statistics of 1926 that with an increase in production of 13,000,000 bbl., there was nevertheless a lowering of both crude and gasoline stocks. It was the first reduction in the last eight years. In 1918, the last year of the war, stocks of crude and refined products were lowered 16,000,000 bbl., but in the following seven years stocks were increased 350,000,000 bbl., due largely to the phenomenal crop of major pools discovered in 1923. The big pools of that year coming as they did through some curious coincidence unprecedented in the oil industry, not only piled up a sudden increase of stocks at a time of large imports but they continued to add their quota to an increase of storage until 1926. With an increase in crude production, according to the Oil and Gas Journal, from 760,000,000 bbl. in 1925 to 773,000,000 bbl. in 1926, and an increase in cracking facilities of about 30 per cent., there was a draft on storage of 22,300,000 bbl. of crude and 1,000,000 bbl. of refined. Crude and refined changed from a stock surplus of 29,130,000 bbl. in 1925, to a deficit of 23,300,000 bbl. in 1926, or a differential total of 52,430,000 bbl. With a stock reserve of 541,700,000 bbl. of crude and refined oil in 1925, the amount drawn from storage was not large in percentage but it marked an important contrast with previous years. It meant a year of stability in prices and a sound condition in the industry. The indicated domestic demand increased from 695,120,000 in 1925 to 743,360,000 in 1926, (7 per cent.), 1 per cent. of which was due to California fires. Most of the gain in consumption was due to the increased demand for gasoline. There was little comparative change in the combined imports of crude and refined oil. There was an increase in exports of 17,200,000 bbl. (1.5 per cent). A petroleum balance sheet for 1926 and a comparativl sheet for the last two years, production in the United States by major districts and pools, and a list of imports are given in Tables 1 to 5, inclusive.